Hippocampal subfield surface deformity in nonsemantic primary progressive aphasia. Issue 1 (1st March 2015) - Christensen, Adam; Alpert, Kathryn; Rogalski, Emily; Cobia, Derin; Rao, Julia; Beg, Mirza Faisal; Weintraub, Sandra; Mesulam, M.‐Marsel; Wang, Lei
Abstract: Background: Alzheimer neuropathology is found in almost half of patients with nonsemantic primary progressive aphasia (PPA). This study examined hippocampal abnormalities in PPA to determine similarities to those described in amnestic Alzheimer disease. Methods: In 37 PPA patients and 32 healthy controls, we generated hippocampal subfield surface maps from structural magnetic resonance images and administered a face memory test. We analyzed group and hemisphere differences for surface shape measures and their relationship with test scores and APOE genotype. Results: The hippocampus in PPA showed inward deformity (CA1 and subiculum subfields) and outward deformity (CA2–4 + dentate gyrus subfield) and smaller left than right volumes. Memory performance was related to hippocampal shape abnormalities in PPA patients, but not controls, even in the absence of memory impairments. Conclusions: Hippocampal deformity in PPA is related to memory test scores. This may reflect a combination of intrinsic degenerative phenomena with transsynaptic or Wallerian effects of neocortical neuronal loss.